ANALYSIS OF LAND AND BUIDING TAX COLLECTION IN PONTIANAK CITY (CASE STUDY IN KOTA BARU VILLAGE, SOUTH PONTIANAK SUB-DISTRICT) - B61111019, MUTIA SARI TILAWANI (Jurnal Ekonomi Daerah (JEDA), 2016)
This research is entitled “Analysis of Land and building tax collection in Pontianak city (Case Study In Kota Baru Village, South Pontianak Sub-district)’’. The problembs formulated in this research come from the fact that target of Land Building tax (PBB) set by the Pontianak City Government especially Kota Baru Village, South Pontianak Sub-district, has not been archived. This the result of the fee collection system applied by Kota Baru Village. This research seeks to examine a number of Aspectsthat are closely related with it, namely: tax collection counducted with the Principle of ease of Administration that discusses certainty, efficiency, convenience and simplicity. Data were obtained using snow ball samplingof key informants who provided detailed information. The collection of research materials was conducted thro in-depth interviews, observations and documentation. The research findings show that the tax collection system still relies on the presence of taxpayers to process of their own administration at the tax and Revenue office with regard to tax subject, tax object, and PBB payers. This reduced the efficiency of tax collection. Tax collection can run wellwith a network development system related to Land and Building tax (PBB) which is connected to BPN, The Agency for licensing Servisces and Investment.